The Impact of COVID-19 on women - United Nations (United Nations Entity for Gender Equality and the Empowerment of Women (UN Women); United Nations Secretariat, 2020)
The year 2020, marking the twenty-fifth anniversary of the Beijing Platform for Action, was intended to be ground-breaking for gender equality. Instead, with the spread of the COVID-19 pandemic, even the limited gains made in the past decades are at risk of being rolled back. The pandemic is deepening pre-existing inequalities, exposing vulnerabilities in social, political and economic systems which are in turn amplifying the impacts of the pandemic. Across every sphere, from health to the economy, security to social protection, the impacts of COVID-19 are exacerbated for women and girls simply by virtue of their sex. This policy brief by the UN Secretary-General explores how women and girls’ lives are changing in the face of COVID-19, and outlines suggested priority measures to accompany both the immediate response and longer-term recovery efforts.
Keywords: 2000 à aujourd'hui; 2020-2029; covid-19; discipline; droit; droits des femmes*; droits humains; pandémie; projet charge mentale; périodes historiques; santé; science politique et droit; thématiques; violences; violences sexistes et sexuelles

Women, gender equality and climate change - United Nations (2009)
Detrimental effects of climate change can be felt in the short-term through natural hazards, such as landslides, floods and hurricanes; and in the long-term, through more gradual deg radation of the environment. The adverse ef fects of these events are already felt in many areas, including in relation to, inter alia, ag riculture and food security; biodiversity and ecosystems; water resources; human health; human settlements and migration patterns; and energy, transport and industry. In many of these contexts, women are more vulnerable to the effects of climate change than men—primarily as they constitute the majority of the world’s poor and are more dependent for their livelihood on natural re sources that are threatened by climate change. Furthermore, they face social, economic and political barriers that limit their coping ca pacity. Women and men in rural areas in developing countries are especially vulnerable when they are highly dependent on local natural resources for their livelihood. Those charged with the responsibility to secure water, food and fuel for cooking and heating face the greatest challenges. Secondly, when coupled with unequal access to resources and to decision-making processes, limited mobility places women in rural areas in a position where they are disproportionately affected by climate change. It is thus important to identify gender-sensitive strategies to respond to the environmental and humanitarian crises caused by climate change.1
Keywords: 2000 à aujourd'hui; 2000-2009; changements climatiques; discipline; droit; développement international; environnement; femmes agricultrices; projet charge mentale; périodes historiques; santé; science politique et droit; sécurité alimentaire; thématiques; travail